Efetividade do acompanhamento de empresas nascentes em incubadoras de base tecnológica - Carla Danielle Araújo Costa (2023)
The purpose of the Business Incubators (IEBT) is to house companies that have products generated from the results of applied research. When they emerged in the 1930s, offering physical infrastructure at low cost was the main differential identified by entrepreneurs when joining an IEBT. Over time, the offer of shared resources was added, such as meeting rooms, secretarial services, general-purpose equipment. Currently, these resources alone are not enough to generate value. Networking promotion is one of the strategies to leverage business. But dealing with internal aspects, how do they need to organize themselves to be able to generate value for entrepreneurs? What internal aspects should be considered so that IEBTs can deliver more than physical space and thus meet their customers' expectations? Thus, the objective of this dissertation is to identify factors that influence this effectiveness, based on two cases, giving more objectivity to generic statements about “services that add value”. Documental survey, visits, face-to-face and videoconference interviews were some of the strategies used to carry out the study, with Grounded Theory (GT) being the methodological approach chosen for its conduction. During the course, several actors were involved: people working in the incubators, coordinators and former coordinators, as well as entrepreneurs who went through the processes. Through the two cases, IEBT A and IEBT B, it was possible to know the processes, raise important factors related mainly to the pre-incubation programs, incubation, and the general functioning of the incubators. In the end, it was possible to point out as effective factors for the contexts addressed: the construction of a work methodology based on the reality of the incubated businesses; close monitoring of business mainly by IEBT B; the establishment of strategic partnerships; fostering an entrepreneurial environment, both internally and externally. As for the ineffective ones: the high turnover of members, and the rigidity of processes based on excessive certifications/standards.